2020
DOI: 10.3389/fnins.2020.00374
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Imaging of Markers of Current Flow and Neurophysiological Changes During tDCS

Abstract: Despite being a popular neuromodulation technique, clinical translation of transcranial direct current stimulation (tDCS) is hampered by variable responses observed within treatment cohorts. Addressing this challenge has been difficult due to the lack of an effective means of mapping the neuromodulatory electromagnetic fields together with the brain's response. In this study, we present a novel imaging technique that provides the capability of concurrently mapping markers of tDCS currents, as well as the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In our experiments, DE-EPI MRI revealed significant tDCS current-induced magnetic fields for both Active-stimulation montages in regions encompassing the left DLPFC (BA 46 and BA 9). Recent studies have compared magnetic field measurements and simulations and found good agreement 53 , 57 , 61 , 71 . However, there are still concerns regarding simulations (e.g.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…In our experiments, DE-EPI MRI revealed significant tDCS current-induced magnetic fields for both Active-stimulation montages in regions encompassing the left DLPFC (BA 46 and BA 9). Recent studies have compared magnetic field measurements and simulations and found good agreement 53 , 57 , 61 , 71 . However, there are still concerns regarding simulations (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Note that the current-induced magnetic fields used in the analysis were corrected for stray-fields following the approach of Goksu et al 57 , 58 (described in Supplementary material S6 ). A confound-analysis was also performed for the BOLD data (following the approach of Jog et al 53 , shown in Supplementary Fig. S12 ), and indicated that the measured tDCS-induced BOLD-signal change was likely neurophysiological in origin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations